Higher Education Equity Policies across the Globe - Salmi, Jamil (International Higher Education, 2019)
The article presents the principal results of an international survey aiming at assessing the nature and extent of policy commitments of national governments to address inequalities in access to and success in higher education. It looks at evolving definitions of equity target groups, reviews the principal instruments on which governments rely to eliminate barriers to access and success for all social groups, and proposes a benchmarking of countries from the viewpoint of the consistency between their policy objectives and actual commitments to equity in higher education.